2003
DOI: 10.1208/pt040222
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the hydrodynamic conditions in the united states pharmacopeia paddle dissolution apparatus

Abstract: KEYWORDS: computational fluid dynamics (CFD), USP paddle apparatus, dissolution, hydrodynamics, modeling The objective of this work was to examine the feasibility of developing a high-performance computing software system to simulate the United States Pharmacopeia (USP) dissolution apparatus 2 (paddle apparatus) and thus aid in characterizing the fluid hydrodynamics in the method. The USP apparatus was modeled using the hydrodynamic package Fluent. The Gambit program was used to create a "wireframe" of the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 14 publications
5
81
2
1
Order By: Relevance
“…Drug release of a poorly soluble drug like EFV, as used in the study, is usually driven more by the medium than by the formulation ingredients. Discriminatory dissolution profiles are highly desirable for distinguishing between products showing differences in pharmaceutical attributes (formulation or manufacturing process differences) as is the case in the present study, wherein the difference in formulation was only with respect to the disintegrant used (10)(11)(12)(13). Figure 1 shows the dissolution profile of 600-mg EFV tablet in water containing different concentrations of SLS containing CP as disintegrant.…”
Section: In Vitro Dissolution Studiesmentioning
confidence: 89%
“…Drug release of a poorly soluble drug like EFV, as used in the study, is usually driven more by the medium than by the formulation ingredients. Discriminatory dissolution profiles are highly desirable for distinguishing between products showing differences in pharmaceutical attributes (formulation or manufacturing process differences) as is the case in the present study, wherein the difference in formulation was only with respect to the disintegrant used (10)(11)(12)(13). Figure 1 shows the dissolution profile of 600-mg EFV tablet in water containing different concentrations of SLS containing CP as disintegrant.…”
Section: In Vitro Dissolution Studiesmentioning
confidence: 89%
“…Differences in the dimensions result in measurable differences in both the paddle tip-vessel wall clearance and in the volume of dissolution media surrounding the paddle. It has been shown that heterogeneous shear rates exist in the hemispheric region of the dissolution vessel (10,11). Given the differences in both the paddle-vessel wall clearance and in the volume of dissolution media surrounding the paddle, hydrodynamics in the hemispheric region of the vessel could be influenced by variability of the dimensions of this critical region of the dissolution vessel.…”
Section: Discussionmentioning
confidence: 99%
“…Recirculation loops have been identified in both the upper and lower sections of the vessel, with a weak positive axial flow under the impeller in the center of lower part of the vessel. Overall fluid velocity values and shear rates in the vessel base are very low, especially at the center of the vessel base compared to other regions of the vessel (13,21,(24)(25)(26)(27).…”
Section: General Flow Featuresmentioning
confidence: 94%
“…Under the standard operating conditions mandated by the dissolution test procedure, with no tablets present in the vessel, the shear strain environment in USP Apparatus 2 is highly heterogeneous with strain rate and fluid velocities varying significantly along the vessel base (21,(24)(25)(26)(27)29). These heterogeneous hydrodynamic conditions are present in the vessel base region where a dosage form is likely to be located.…”
Section: Hydrodynamics In the Lower Hemispherical Section Of The Vesselmentioning
confidence: 99%